Hatter M. Vol. 2, Mad with wonder - Beddor, Frank (Beddor, Frank. Looking glass wars, 2009)
Hatter follows the Glow from London to the battlefields of America's Civil War in search of the Princess who must some day be Queen. The America that Hatter encounters is a sprawling, wounded, boiling landscape of innocence and energy run amok. The war is tearing the country apart, yet Hatter must maintain his sanity in this maelstrom of holy rollers, child healers, prophetic snake handlers, deranged outlaws, and passionate southern belles. As Hatter searches he learns he is not the only Wonderland presence that has found its way to the Promised Land. Queen Redd's black imagination is fueling the Civil War and threatening our world with her evil!